The role of the psychoeducation for family preparedness application on psychological preparedness and functional activities of families post-disaster: A community intervention study - Retna Tri Astuti; Mohammad Fanani; Munawir Yusuf; Eny Lestari; Suminah (Physical Therapy Journal of Indonesia, 2025)
Background: Families residing in disaster-prone areas are at increased risk of psychological and functional disruption during and after disasters. This study aimed to evaluate the effectiveness of the psychoeducation for family preparedness (PEKA) application in improving psychological preparedness and family functional activities among households in disaster-prone communities. Methods: A quasi-experimental pretest-posttest control group design was conducted with 60 purposively selected families. The intervention group utilized the PEKA application for 4 weeks, a practical and user-friendly tool that comprises six interactive modules covering disaster education, emotional regulation, evacuation planning, communication, daily functionality, and journaling. Validated instruments measured psychological preparedness and functional activity. Data were analyzed using paired t-tests and ANCOVA. Results: After the intervention, the intervention group showed significant improvements in both psychological preparedness (Mean ± SD: 66.2 ± 7.8 to 81.4 ± 6.9; p < 0.001) and functional activities (62.0 ± 6.3 to 75.6 ± 7.1; p < 0.001), while the control group did not show significant changes. ANCOVA revealed significant between-group differences for both psychological preparedness (F (1,57) = 18.96; p < 0.001; η² = 0.248) and functional activity (F (1,57) = 12.21; p = 0.001; η² = 0.176). Application engagement was high, with 85% of participants completing more than 80% of the modules. Conclusion: The PEKA application was an effective digital intervention that enhances both the psychological preparedness and functional capacity of families in disaster-prone areas. Integrating psychoeducational content with interactive tools and professional support can strengthen family resilience and serve as a scalable model for community-based disaster risk reduction.